Economics of Management of Agro Based Industry With Reference to Coconut: Driving Economic Growth through Agro-based Industries (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The agro based industry is regarded as an extended arm of agriculture.The development of the agro industry can help stabilize and make agriculturemore lucrative and create employment opportunities both at the production andmarketing stages. The broad-based development of the agro-products industry wasimproving both the social and physical infrastructure of India. Since it would cause diversification and commercialization ofagriculture, it was thus enhance the incomes of farmers and create foodsurpluses. The agro-industry mainly comprises of the post-harvestactivities of processing and preserving agricultural products for intermediate orfinal consumption. It is a well-recognized fact across the world, particularlyin the context of industrial development that the importance of agro-industriesis relative to agriculture increases as economies develop. It should beemphasized that ‘food’ is not just produce. Food also encompasses a widevariety of processed products. It is in this sense that the agro-industry is animportant and vital part of the manufacturing sector in developing countriesand the means for building industrial capacities.